Analisis Faktor Pengaruh Minat Berinvestasi Generasi Z Pada Reksadana Syariah - Rahmi, Rifa Aulia; Supriyanto, Trisiliadi; Nugrahaeni, Siwi (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
Generation Z is expected to be a long-term investment segment by OJK. Even though they have started investing, most of the Z generation still feel they are limited to basic knowledge. The purpose of this study was to determine the effect of financial literacy, motivation, religiosity, and perceived ease on interest in investing in Jabodetabek Generation Z in sharia mutual funds. The quantitative approach is the research method chosen to conduct this research. The sample used is 100 people who are Generation Z who are in the Greater Jakarta area and have an understanding of sharia mutual funds. The use of Likert scale is used in the questionnaire to obtain data. This study uses multiple linear regression analysis which is supported by validity and reliability tests, classical assumption tests, and hypothesis tests consisting of F test, T-test, and coefficient of determination test assisted by SPSS version 25 software. The results of this study indicate a large influence of financial literacy, motivation, religiosity, and perceived ease of interest in investing in Jabodetabek Generation Z. in sharia mutual funds by 58.3%, the remaining 41.7% is influenced by other factors, while financial literacy, motivation, and perceived convenience have a significant effect on interest in investing in Jabodetabek generation Z in sharia mutual funds, but the religiosity variable does not significantly affect investment interest in generation Z in sharia mutual funds.